2014
DOI: 10.1159/000365922
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Global Positioning System on the Driving Performance of People with Mild Alzheimer's Disease

Abstract: Introduction: The initial symptoms of Alzheimer's disease (AD) include attention deficits, memory loss and deficiencies in topographic and spatial orientation. People with AD may have way-finding difficulties in driving due to the deterioration of their navigation ability. Although the use of the Global Positioning System (GPS) has been proven to be a useful aid for older people in driving, there is no evidence to suggest that the benefit could extend to drivers with AD. Aim: This study aims to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 41 publications
0
51
0
Order By: Relevance
“…Only two studies were found that examined ways to help individuals with dementia drive more safely. One study examined the effect of ChEI (Daiello et al, 2010) and the other examined different types of GPS displays (Yi et al, 2015). The lack of intervention studies is possibly due to the assumption that once individuals are diagnosed with AD, they cease driving.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies were found that examined ways to help individuals with dementia drive more safely. One study examined the effect of ChEI (Daiello et al, 2010) and the other examined different types of GPS displays (Yi et al, 2015). The lack of intervention studies is possibly due to the assumption that once individuals are diagnosed with AD, they cease driving.…”
Section: Discussionmentioning
confidence: 99%
“…Global Positioning Systems. One study conducted by Yi, Lee, Parsons, and Falkmer (2015) examined the effect of visual and verbal cues plus verbal global positioning systems (GPS) on a simulated driving test in individuals with very mild to mild AD. Results showed a significant difference between the GPS conditions, with the best driving performance in the audio-only condition.…”
Section: Interventions For Driving and Driving Cessationmentioning
confidence: 99%
“…For example, there is evidence from one study that auditory only global positioning satellites help persons with dementia find their way in outdoor environments while driving (Yi, Lee, Parsons & Falkmer, 2015). It is possible that similar technology could be used in complex indoor environments.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…Contrary, no differences in number of crashes between AD patients and controls have also been reported [83]. AD patients performed best when single, simple auditory-only driving navigation instructions were used compared to visual plus audio or visual-only instructions [84]. …”
Section: Resultsmentioning
confidence: 99%
“…The symptoms of simulator sickness are typically less severe than motion sickness and tend to decrease with multiple exposure and time [94, 95]. Dropouts in simulator studies have been related to simulator sickness, with up to one-third of the participants experiencing signs of simulator sickness [64, 84, 91]. The duration and configuration of the driving scenario influence this dropout rate [96].…”
Section: Resultsmentioning
confidence: 99%